Reccurent episodes of vomiting and hyperpigmentation---Addison,s disease, a case report (TAJ: Journal of Teachers Association, 2018)
Addison’s disease can remain unrecognized for a longtime until acute adrenal insufficiency is precipitated by an acute stress. Addison’s disease usually presents with non-specific symptoms like fatigue, nausea, vomiting, hyperpigmentation and generalized weakness. These symptoms are most often ignored or misinterpreted with other more common diseases. This is the major reason that this disease is under-diagnosed. Therefore, to establish a diagnosis high index of suspicion is needed.We are reporting a case of 10 years old boy who presented with recurrent episode of severe vomiting and generalized weakness. This kind of presentation of Addison’s disease is rather unusual and mainstay of diagnosis is clinical based.TAJ 2016; 29(2): 66-69